The causal role of circulating inflammatory markers in osteoporosis: a bidirectional Mendelian randomized study - Dong, Qiu; Wu, Jiayang; Zhang, Huaguo; Luo, Liangping; Wu, Wenrui (Frontiers in Immunology, 2024)
Background Osteoporosis (OP) associated with aging exerts substantial clinical and fiscal strains on societal structures. An increasing number of research studies have suggested a bidirectional relationship between circulating inflammatory markers (CIMs) and OP. However, observational studies are susceptible to perturbations in confounding variables. In contrast, Mendelian randomization (MR) offers a robust methodological framework to circumvent such confounders, facilitating a more accurate assessment of causality. Our study aimed to evaluate the causal relationships between CIMs and OP, identifying new approaches and strategies for the prevention, diagnosis and treatment of OP. Methods We analyzed publicly available GWAS summary statistics to investigate the causal relationships between CIMs and OP. Causal estimates were calculated via a systematic analytical framework, including bidirectional MR analysis and Bayesian colocalization analysis. Results Genetically determined levels of CXCL11 (OR = 0.91, 95% CI = 0.85–0.98, P = 0.008, PFDR = 0.119), IL-18 (OR = 0.88, 95% CI = 0.83–0.94, P = 8.66×10–5, PFDR = 0.008), and LIF (OR = 0.86, 95% CI = 0.76–0.96, P = 0.008, PFDR = 0.119) were linked to a reduced risk of OP. Conversely, higher levels of ARTN (OR = 1.11, 95% CI = 1.02–1.20, P = 0.012, PFDR = 0.119) and IFNG (OR = 1.16, 95% CI = 1.03–1.30, P = 0.013, PFDR = 0.119) were associated with an increased risk of OP. Bayesian colocalization analysis revealed no evidence of shared causal variants. Conclusion Despite finding no overall association between CIMs and OP, five CIMs demonstrated a potentially significant association with OP. These findings could pave the way for future mechanistic studies aimed at discovering new treatments for this disease. Additionally, we are the first to suggest a unidirectional causal relationship between ARTN and OP. This novel insight introduces new avenues for research into diagnostic and therapeutic strategies for OP.